GREEN INNOVATION AND STAKEHOLDERS’ SATISFACTION IN DEPOSIT MONEY BANKS IN OWERRI - Njoku, Kenneth Chukwudi PhD, Udo-Orji, Chidinma, PhD; Adioha, Lynda Ekwutosi, PhD (Journal of the Management Sciences, 2024)
Ideally, organizations that go green appear to stand better chances of being the true custodians of sustainability in predetermined corporate outcomes. However, a lot of research gaps have been observed in the area of green innovation in business organizations. This situation calls for this study on green innovation as a predictor of stakeholders’ satisfaction in Deposit Money Banks in Owerri. The objectives of the study are to examine the relationship between use of solar panels(USP) and employee satisfaction; evaluate the level of correlation between use of solar panels(USP) and customer satisfaction; assess the extent to which eco-friendly business conferences(EBC) influences employee satisfaction and determine the level of correlation between eco-friendly business conferences(EBC) and customer satisfaction. The study develops a problem statement that captures the research gaps which call for the empirical investigation. The study is guided by four research objectives, four research questions and four hypotheses. Empirical reviews are used to beef up the study. The research employs the survey research design in the research. A five-point Likert Scale structured questionnaire is the major instrument for data collection. The researchers determined the validity of the instrument by showing the questionnaire to research experts for their corrections and inputs. The study uses Cronbach Alpha statistic for obtaining 0.86 as the reliability ratio of the survey instrument. The research commits data analysis to descriptive statistics of mean and standard deviation and employs correlation analysis for testing hypotheses. The findings show that there is a significant relationship between use of solar panels(USP) and employee satisfaction; there is significant level of correlation between use of solar panels(USP) and customer satisfaction; it is to a great extent that eco-friendly business conferences(ESC) influences employee satisfaction and there is significant level of correlation between eco-friendly business conferences(ESC) and customer satisfaction. The study concludes that green innovation predicts stakeholders’ satisfaction in Deposit Money Banks in Owerri. The study recommends that management of Deposit Money Banks should always use solar panels to eliminate severe noise pollution for greater stakeholders’ satisfaction. Deposit Money Banks should always use zoom and allied facilities for their conferences since such is ecofriendly